Kajian Literatur Strategi Pengelolaan Human Resources Dalam Upaya Meningkatkan Kinerja Dan Motivasi Karyawan Melalui Balanced Scorecard - Hasya Febrianty, Aca; Asriati, Nuraini (LP2M Universitas Perjuangan Tasikmalaya, 2024)
This study aims to examine the strategy of human resource management (HR) through the implementationof the Balanced Scorecard (BSC) in an effort to improve employee performance and motivation. TheBalanced Scorecard consists of four main perspectives, namely financial, customer, internal businessprocesses, and learning and growth. Through a literature review, it was found that the implementation ofBSC in HR management can improve employee performance by providing a more transparent andintegrated assessment system, and facilitating competency development through continuous learninggrowth. HR through the Scorecard can also help control the cost of creating company value, assess HRcontributions to strategy implementation, and support organizational change and formation. In addition,BSC has also proven effective in increasing employee motivation by creating a fair evaluation system andencouraging innovation. However, challenges such as resistance to change also need to be anticipated.Overall, the implementation of BSC in HR management has great potential to support long-termachievements through more effective and structured HR management.